العوامل المحددة للإفصاح البيئي للمؤسسات الاقتصادية الجزائرية - دراسة تطبيقية للمؤسسات الصناعية للفترة (2018-2015-) - (مجلة الواحات للبحوث والدراسات, 2025)
The Study Aims To Test And Identify The Factors Affecting The Environmental Disclosure Of Industrial Enterprises To Reduce Environmental Impacts And Damages And To Analyze The Importance Of Making Environmental Information Available To Stakeholders And Society, And To Reach The Desired Results, The Descriptive Approach Was Used To Determine The Theories Explaining The Environmental Disclosure In Economic Institutions, And We Adopted The Experimental Approach On A Model Analysis The Content In Measuring The Environmental Disclosure, In Addition To The Multiple Linear Regression, The Impact Of External And Institutional Factors On The Environmental Information Disclosed By Algerian Industrial Enterprises During The Extended Period (2015-2018).The Results Of The Study Concluded That The Factors Affecting The Environmental Disclosure Of Environmental Information Were Identified, Represented By The Governmental Authority Due To Its Environmental Regulations And Laws, And The Implementation Mechanisms That The Government Authority Has Over The Study Sample Institutions By Using Environmental Collection, And The Size Due To The Environmental Impacts That It Leaves, And Highlights The Importance Of The Study To Consider Environmental Disclosure As A Value Within The Institution, Which Reflects Its Interest In Environmental Responsibility, With The Need To Strengthen Cooperation With All Of The Governmental Authority, Stakeholders, And Society To Achieve The Environmental Performance Of Algerian Industrial Enterprises.Key Words-  Environmental Disclosure, Environmental Information, External Factors, Institutional Factors, Industrial Enterprises.